A invenção de Torres: do Balneário Picoral à criação da Sociedade Amigos da Praia de Torres - SAPT (1910-1950) - Cardoso, Eduardo Mattos (Universidade do Vale do Rio do Sinos, 2008)
This research identifies and analyzes the factors that conditioned social, cultural, economic and spatial organization transformations occurred from the 1910 to the 1950 decades in Torres, Porto Alegre elite members’ main beach resort. This analysis focuses on the different symbolic resources established by the social groups within the beach space. A description of the scenario elevation is made by considering the traveler’s view along the centuries – since the invention of the Torres beach starts from its natural beauties and geographic location and parallels to the transformation of the coast in a beach that follows the European model, which considers the beach firstly as a therapeutic space and then as a leisure and social distinction place provided by the free times. It is the establishment of a new view regarding the beach, the social invention of nature through the interpenetration between nature and culture (and its appropriation) which will result in social power. Besides, it will give Torres beach ot
Keywords: distinção social; elite porto-alegrense; praia; sociabilidade; Torres; Porto Alegre elite; sociability; social distinction; beach; Ciências Humanas